Foregone : a novel - Banks, Russell, 1940- (Ecco, an imprint of HarperCollinsPublishers, 2021)
A septuagenarian leftist documentary filmmaker gives a last interview from his mythologized life to a former star student to whom he discloses his experiences as a draft dodger who fled to a new life in Montreal.